Photoelectron spectroscopy of large water clusters ionized by an XUV comb. (26th June 2020) - Trabattoni, Andrea; Colaizzi, Lorenzo; Ban, Loren; Wanie, Vincent; Saraswathula, Krishna; Månsson, Erik P; Rupp, Philipp; Liu, Qingcao; Seiffert, Lennart; Herzig, Elisabeth A; Cartella, Andrea; Yoder, Bruce L; et al.
Abstract: Detailed knowledge about photo-induced electron dynamics in water is key to the understanding of several biological and chemical mechanisms, in particular for those resulting from ionizing radiation. Here we report a method to obtain photoelectron spectra from neutral water clusters following ionization by an extreme-ultraviolet (XUV) attosecond pulse train, representing a first step towards a time-resolved analysis. Typically, a large background signal in the experiment arises from water monomers and carrier gas used in the cluster source. We report a protocol to quantify this background in order to eliminate it from the experimental spectra. We disentangle the accumulated XUV photoionization signal into contributions from the background species and the photoelectron spectra from the clusters. This proof-of-principle study demonstrates feasibility of background free photoelectron spectra of neutral water clusters ionized by XUV combs and paves the way for the detailed time-resolved analysis of the underlying dynamics.